Determinants of Industrial Output for the Manufacturing Industries in Jordan: Canonical Cointegration Regression Model (CCR Model) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This paper aims to analyze the determinants of industrial output )added value of manufacturing industries) in Jordan, by measuring the impact of macroeconomic and monetary variables represented by the industrial exports, imports of capital goods, and production inputs (except raw materials), taxes on production, energy prices in terms of fuel prices, inflation rates, and interest rates on the added value of manufacturing industries in Jordan using quarterly data during the period (2009-2022). The study employed the methodology of the standard co-integration regression model (CCR MODEL) since it is the appropriate method within the characteristics of the variables used. The results showed that there is a statistically significant impact of the variables used on the added value of manufacturing industries, as they explained that industrial exports and imports of production inputs and capital goods have a strong impact on increasing industrial growth rates, in contrast with the impact of high interest rates in reducing industrial output, and it indicated the level of impact of energy prices in reducing the competitiveness of manufacturing industries, besides the impact of taxes imposed on industrial companies in increasing the burdens of the industrial sector by bearing the additional costs on production. The study recommends the need for national efforts to be intensified and focused on the real factors that support manufacturing industries, specifically production costs of all kinds (energy, financing, employment) in order to have a significant positive impact on the economy and civil society through increasing employment, lowering unemployment rates, and increasing added value to the country's economy.
Keywords: Industry; Jordan; Macroeconomic Variables; Manufacturing